Pelatihan Pengembangan Soal Literasi Framework Asesmen Kompetensi Minimum (AKM) untuk Guru-Guru IPA SMP Kota Palembang - Susanti, Rahmi; Destiansari, Elvira; Anwar, Yenny; Riyanto, Riyanto; Okta Cahyaningrum, Alya; Septiana, Resma; Aliza Anggraini, Nur; Innayatullah, Fatiah; Arundina, Asyifa; Yulianti, Rica; Riski, Muhammad; Dhelcia Bayumi, Karina (Jurnal SOLMA, 2025)
Background: National Assessment, including AKM, is designed to measure students' literacy and numeracy skills. However, many teachers find it difficult to develop AKM-based literacy questions due to lack of training. This training aims to improve teachers' understanding and skills in compiling literacy questions based on the AKM Framework through systematic training and mentoring. Methods: Phase I (Preliminary Study): observations, interviews, questionnaires, and literature studies were conducted to analyze teachers' knowledge related to AKM Framework literacy questions and prepare training materials. Phase II (Implementation): a workshop to provide understanding and practice in developing AKM Framework literacy questions with simulations and feedback. Phase III (Mentoring and Guidance): continuously assisting teachers in developing literacy questions. Phase IV (Evaluation): through monitoring, evaluation of training results, and follow-up for improvement. The target of this activity is 40 junior high school science teachers from the Palembang City Science MGMP, who are expected to be able to improve their pedagogical skills and become facilitators in schools. Evaluation was conducted through pre-test, post-test, question development assignments, and feedback questionnaires related to the training. Results: The post-test results showed an increase in teachers' understanding of AKM in the "very good" category reaching 36.8%. The responses of the training participants showed high satisfaction, especially in terms of design, duration, and method of delivering the material, with an average of 80-90% of participants giving positive assessments. Conclusion: This training is expected to not only support the implementation of AKM.